The Biomedical Research in Italy and the role of BIBLIOSAN - Toni, Franco (Qualitative and Quantitative Methods in Libraries, 2019)
BIBLIOSAN is a system funded in 2003 by the Italian Ministry of Health and whose aim is to achieve a cooperative network amongst more than 60 libraries of the Italian biomedical research institutes and hospitals. The paper aims to provide an overview of the most relevant issues faced during the past 15 years, on the ways to deal with them and on the adopted solutions. The network is now able to assure a shared catalogue of the collections owned by each partner, a tested and efficient system for the exchange and delivery of documents and articles, the organization of a relevant number of e-learning and on-site training courses for users and librarians and overall to guarantee the subscriptions to about 10,000 e-journals published by all the most important scientific publishers such as Elsevier, Wiley, Nature publishing Group, etc. A rapid glance to the possible future evolutions and improvements of the system will be also provided.